Dismantling Political Dynasties: Transformation of Pancasila Democracy in the Context of Family Power (JED (Jurnal Etika Demokrasi), 2024)
Dynastic politics is still a dominant phenomenon in Indonesia's political system, showing that political power often belongs to certain families. In this context, Pancasila democracy continues to transform, facing major challenges in maintaining pluralism and justice in the political process. This study aims to investigate the impact of political dynasties on the transformation of Pancasila democracy and explore efforts that can be made to overcome the dominance of family power in politics. This research uses a qualitative approach with content analysis techniques to examine related literature, empirical data, as well as interviews with political and civil society experts who have direct experience with political dynasties. The results showed that political dynasties had a significant impact on Pancasila democracy, reducing people's political participation, reducing pluralism, and causing injustice in the distribution of power. However, the research also revealed several civil society initiatives and policy reforms that might reduce the dominance of political dynasties and strengthen Pancasila democracy. The implication of this research is the need for joint efforts from governments, civil society, and international institutions to address the problem of political dynasties in Indonesia's political system. Policy reforms are needed that support inclusive political participation, reduce wealth gaps and access to political power, and strengthen political oversight and accountability mechanisms to ensure that Pancasila democracy continues to function by its principles.